2017
DOI: 10.1016/j.omtm.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability as a Determinant of AAV Serotype Identity

Abstract: Currently, there are over 150 ongoing clinical trials utilizing adeno-associated viruses (AAVs) to target various genetic diseases, including hemophilia (AAV2 and AAV8), congenital heart failure (AAV1 and AAV6), cystic fibrosis (AAV2), rheumatoid arthritis (AAV2), and Batten disease (AAVrh.10). Prior to patient administration, AAV vectors must have their serotype, concentration, purity, and stability confirmed. Here, we report the application of differential scanning fluorimetry (DSF) as a good manufacturing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 52 publications
15
112
0
Order By: Relevance
“…This suggests that even while existing as a highly pressurized capsid, P22 can still be isovolumetrically distorted to a greater extent than the rigid AAV capsid by the shear forces of the liquid. Thermal and proteolytic stabilites of AAVs have shown that these capsids are extremely resistant to environmental changes [33,34] and our QCM-D results substantiate these results. The low rigidity of PBCV among compared to other viruses was expected due to the greater diameter and emphasizes that rigidity is not a simple outcome of subunit number.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This suggests that even while existing as a highly pressurized capsid, P22 can still be isovolumetrically distorted to a greater extent than the rigid AAV capsid by the shear forces of the liquid. Thermal and proteolytic stabilites of AAVs have shown that these capsids are extremely resistant to environmental changes [33,34] and our QCM-D results substantiate these results. The low rigidity of PBCV among compared to other viruses was expected due to the greater diameter and emphasizes that rigidity is not a simple outcome of subunit number.…”
Section: Discussionsupporting
confidence: 85%
“…Our experiments show that the rigidities of AAV capsids vary significantly with serotype. Thermal and proteolytic stabilities of empty and genome filled AAVs have also been well studied and have shown similar differences [33,34]. On the other hand, nanoindentation studies of AAV capsids using AFM pointed to a higher propensity for deformation of the empty forms [35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated that AAV serotypes are different in their thermal stability, with rAAV2 being the least thermal stable and rAAV5 being the most thermal stable. In PBS buffer, the melting temperature (Tms) of different AAV serotypes range from 66.5 up to 89.5 °C 43 . Therefore we choose to heat rAAV samples at 95 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Although AAV is the simplest form of an icosahedral capsid, the intermonomeric interactions occurring within the assembly are considerably complex and contribute to a remarkably stable virion that can withstand appreciably high temperatures (24)(25)(26), a wide range of pH (27), and long shelf-lives (27), while remaining infectious. There is a reasonably high energy barrier associated with assembling this highly stable product, corroborated by the inability of VP monomers to selfassemble (12) and the requirement for AAP, which promotes VP oligomerization to overcome such energy barriers.…”
Section: Discussionmentioning
confidence: 99%